2005
DOI: 10.1002/bit.20446
|View full text |Cite
|
Sign up to set email alerts
|

Cell cycle analysis ofTaxus suspension cultures at the single cell level as an indicator of culture heterogeneity

Abstract: Single cell growth and division was measured via flow cytometry in order to characterize the metabolic variability of Taxus cuspidata suspension cultures, which produce the valuable secondary metabolite Taxol. Good agreement was observed between the cell cycle distribution and biomass accumulation over the batch culture period. Specific growth rates of 0.13 days(-1) by fresh weight and 0.15 days(-1) by dry weight were measured. Elicitation with methyl jasmonate (MJ) significantly decreased both cell cycle prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 62 publications
3
37
0
Order By: Relevance
“…Ketchum and Gibson 1996;Ketchum and Croteau 1998;Yukimune et al 2000;Wu and Lin 2003;Naill and Roberts 2005;Khosroushahi et al 2006;Vongpaseuth and Roberts 2007). This conclusion is further supported by the aforementioned work of Croteau and his associates who succeeded in the isolation of paclitaxel biosynthetic genes of plant origin.…”
Section: A Physical Interaction Merely? the Plausibility Of Horizontasupporting
confidence: 55%
“…Ketchum and Gibson 1996;Ketchum and Croteau 1998;Yukimune et al 2000;Wu and Lin 2003;Naill and Roberts 2005;Khosroushahi et al 2006;Vongpaseuth and Roberts 2007). This conclusion is further supported by the aforementioned work of Croteau and his associates who succeeded in the isolation of paclitaxel biosynthetic genes of plant origin.…”
Section: A Physical Interaction Merely? the Plausibility Of Horizontasupporting
confidence: 55%
“…In Taxus cell cultures, various elicitors have been used to stimulate taxoid production (e.g., Huang et al, 2005;Naill and Roberts, 2005;Qian et al, 2004a,b;Tabata, 2004;Wu and Ge, 2004;Ye et al, 2004). Regarding the elicitation mechanism, there are reports on defense responses such as oxidative burst, NO burst and/or JA by cultured cells of Taxus spp.…”
Section: Introductionmentioning
confidence: 98%
“…Jasmonic acid (JA), methyl jasmonate (MJ) and its derivatives are a family of important signal transducers, and can efficiently stimulate secondary metabolism in plant cells (e.g., Farmer and Ryan, 1990;Gundlach et al, 1992;Naill and Roberts, 2005;. Since the first report regarding the effect of MJ on the accumulation of secondary metabolites in plant cell cultures (Gundlach et al, 1992), more than 100 plant species have been demonstrated to respond to the addition of MJ to the culture medium by accumulating secondary metabolites (Haider et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Jasmonic acid, and its derivatives are a family of important signal transducers, that can efficiently stimulate secondary metabolism in plant cells (Gundlach et al, 1992;Naill and Roberts, 2005;. Since the first report regarding the effect of methyl jasmonate (MJ) on the accumulation of secondary metabolites in plant cell cultures (Gundlach et al, 1992), more than 100 plant species have been demonstrated to respond to the addition of MJ to the culture medium by accumulating secondary metabolites (Haider et al, 2000).…”
Section: Introductionmentioning
confidence: 99%